(untitled) (Global Journal of Management and Business Research, 2022)
The study was conducted to determine the entrepreneurial intention of business students The study used the multiple regression analysis in determining the factors affecting the entrepreneurial intentions of business students All variables in this study which are attitude towards becoming an entrepreneur perceived behavioral control subjective norms and entrepreneurial intention were described as a high by business students